The Effects of Blended Learning and Project-Based Learning on Pre-Service Biology Teachers’ Creative Thinking through Online Learning in the Covid-19 Pandemic (Jurnal Pendidikan IPA Indonesia, 2020)
The purpose of this study was to analyze the effect of Blended Learning (BL) and Project-Based Learning (Pj-BL) on the pre-service teachers’ creative thinking in learning biology. This type of research is a quasi-experimental study with 76 biology education students as research subjects. In its implementation, the experimental class was taught using the BL and Pj-BL approach, the control class is conventional class. The parameters are creative thinking with 4 indicators. Data was collected using pretest and posttest assessments. Data is presented and analyzed descriptively. The results of the study were overall the average score of creative thinking of pre-service teachers in the experimental class was 91 with an N-gain index of 0.62, higher than in the control class (76) with an N-gain index of 0.51. From the results, it could be concluded that Blended Learning and Project-Based Learning are quite influential in increasing the creative thinking ability of pre-service biology teachers, and BL and Pj-BL is quite more effective than conventional in increasing the pre-service teachers’ creative thinking in biology learning.